Heirloom and Hybrid Corn in the American Corn Belt: an Ethnography of Seed Saving Practices - (:unkn) unknown (My University, 2019)
This ethnographic study examines the practices and context of contemporary heirloom corn seed saving practices and projects in the American Corn Belt. It examines heirloom corn conservation and hand pollination practices at Seed Savers Exchange in Decorah, Iowa in 2015. From there the study extends to interviews with heirloom farmers, breeders and gardeners in Wisconsin and Illinois. The findings indicate that the lines between the mainstream and the margins of corn production are highly blurred, and that there is a considerable amount of cross-pollination of ideas and practices between alternative corn farming and dominant industrial hybrid production in the American Corn Belt as they exist in proximity and utilize similar public spaces and resources. The results of these cross-pollinations of ideas are differing visions of sustainability that farmers, breeders and seed savers use to frame their heirloom corn growing projects and maintain the marginal spaces required for them to grow in the Corn Belt. The author explores the histories of hybrids and heirlooms in the Corn Belt and the contemporary evolution of USDA Organic Corn Production to illustrate this point.
Keywords: agrobiodiversity; heirloom corn; in situ conservation; seed saving